Diospyros phuwuaensis (Ebenaceae), a new species from North-Eastern Thailand - Duangjai, Sutee; Rueangruea, Sukid; Phutthai, Thamarat; Middleton, David; Suddee, Somran (Thai Forest Bulletin (Botany), 2020)
Diospyros phuwuaensis, a new species from Phu Wua Wildlife Sanctuary, North-Eastern Thailand is described and illustrated. Photographs, ecological information and an IUCN conservation status are provided. The distinctive morphological characters of the new species and its related species are discussed. Based on cpDNA data, the new species is confirmed as an independent lineage and placed in the Diospyros clade V sensu Duangjai et al. (2009). It has phylogenetic affinities with Diospyros mollis, and then D. fulvopilosa and D. kurzii. Our result supports the assignment of the new species to Diospyros section Kurzella. A revised description and a key to the species of Diospyros section Kurzella is presented.